Utilizing Way of Life (WOL) Animated Videos as a Learning Tool for Islamic Cultural History in Islamic Education at Madrasah - Muhammad Thonthowi Anwar; Irma Suraya (At-Ta'lim : Media Informasi Pendidikan Islam, 2024)
ENGLISH: Utilizing the Way of Life (WOL) Animated Video as a Learning Tool for Islamic Cultural History in Islamic Religious Education at MadrasahObjective: This study examines the utilization of video as a medium for teaching the history of Islamic culture in grade 4 MI Nurul Islam. Method: This research uses the descriptive qualitative method. The data collection method used in this research is the survey method. This research was conducted through a survey using a Google-like tool targeting 30 fourth-grade students of MI Nurul Islam. Results: Data analysis shows 100% answered yes that learning the history of Islamic culture through animated videos is easy. The results showed that all fourth-grade students of MI Nurul Islam responded positively to the animated video learning according to their wishes. Conclusion: Animated video learning is fun and easy to understand, and according to the student's wishes, they positively respond to learning animated video fun. Contribution: This research contributes scientific information in Islamic religious education about using animated video way of life (wool) to teach Islamic cultural history (ski) in schools.INDONESIAN: Pemanfaatan Video Animasi Way of Life (WOL) sebagai Media Pembelajaran Sejarah Kebudayaan Islam pada Mata Pelajaran Pendidikan Agama Islam di MadrasahTujuan: Penelitian ini mengkaji pemanfaatan video sebagai media pengajaran sejarah budayaan Islam di kelas 4 MI Nurul Islam. Metode: Penelitian ini menggunakan metode deskriptif kualitatif, metode pengumpulan data yang digunakan dalam penelitian ini adalah metode survei. Penelitian ini dilakukan melalui survei menggunakan alat sejenis Google yang menyasar 30 siswa kelas IV MI Nurul Islam. Hasil: Analisis data menunjukkan 100% menjawab ya bahwa mempelajari sejarah kebudayaan Islam melalui video animasi itu mudah. Hasil penelitian menunjukkan bahwa seluruh siswa kelas IV MI Nurul Islam memberikan respon positif terhadap pembelajaran video animasi sesuai dengan keinginannya. Kesimpulan: Pembelajaran video animasi itu menyenangkan, mudah dipahami dan sesuai dengan keinginan para siswa dan mereka memberikan respon positif terhadap pembelajaran video animasi menyenangkan. Kontribusi: Penelitian ini berkontribusi sebagai sumber informasi ilmu pengetahuan di bidang pendidikan agama islam tentang pemanfaatan video animasi way of life (wol) sebagai media pembelajaran sejarah kebudayaan islam (ski) di sekolah.